2015
DOI: 10.1210/en.2014-1803
|View full text |Cite
|
Sign up to set email alerts
|

Classical and Membrane-Initiated Estrogen Signaling in an In Vitro Model of Anterior Hypothalamic Kisspeptin Neurons

Abstract: The neuropeptide kisspeptin is essential for sexual maturation and reproductive function. In particular, kisspeptin-expressing neurons in the anterior rostral periventricular area of the third ventricle are generally recognized as mediators of estrogen positive feedback for the surge release of LH, which stimulates ovulation. Estradiol induces kisspeptin expression in the neurons of the rostral periventricular area of the third ventricle but suppresses kisspeptin expression in neurons of the arcuate nucleus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 77 publications
6
59
1
Order By: Relevance
“…Also, one study indicated a downregulation of Kiss1 expression in mHypoA-51 and mHypoA-63 cells after a 4 h E2 treatment, with the decrease less pronounced or lost 24 h post E2 treatment (Kim 2010). A more recent study, however, found an increase in Kiss1 expression in mHypoA-51 cells, after a 24 h E2 treatment (Mittelman-Smith et al 2015). We detected low to no expression of Kiss1, Gh, and Prl in the five cell lines.…”
Section: -B)contrasting
confidence: 70%
See 1 more Smart Citation
“…Also, one study indicated a downregulation of Kiss1 expression in mHypoA-51 and mHypoA-63 cells after a 4 h E2 treatment, with the decrease less pronounced or lost 24 h post E2 treatment (Kim 2010). A more recent study, however, found an increase in Kiss1 expression in mHypoA-51 cells, after a 24 h E2 treatment (Mittelman-Smith et al 2015). We detected low to no expression of Kiss1, Gh, and Prl in the five cell lines.…”
Section: -B)contrasting
confidence: 70%
“…We detected low to no expression of Kiss1, Gh, and Prl in the five cell lines. Previous studies describing Kiss1 expression in mHypoA-51 and mHypoA-63 used an input RNA concentration that was 2.5 times higher than that used in our experiments to prepare cDNA for qPCR experiments (Friedman 2013;Kim 2010;Mittelman-Smith et al 2015), providing a possible explanation for discrepancy among studies regarding detection of Kiss1. Our results indicate an extremely low basal mRNA expression of Kiss1, Gh, and Prl in the lines tested.…”
Section: -B)mentioning
confidence: 93%
“…For example, it may have an effect on the development of follicular system, ovulation, embryo implantation and decidualization of endometrium. 31 Recently, one review sufficiently provided the evidence that the treatment of ovariectomized females with chronic, low-dose estradiol implants for either 7 or 14 days could reverse the decline of kisspeptin in the third ventricle. 29 However, whether the low pregnancy outcomes and implantation failure in IUA are associated with the loss of kisspeptin after trauma to endometrium has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These neurons are prime candidates to integrate estradiol and progesterone information that regulates GnRH secretion underlying the LH surge. Although most of the work on steroid regulation of Kiss1 and its gene, KiSS-1 has focused on estradiol (80,197), there are interesting results that suggest estradiol and neuroP may interact to stimulate Kiss1 in the RP3V (136). First, both ERα and PR are needed for positive feedback of the LH surge (25, 26, 210), and both have been localized in RP3V Kiss1 neurons, but neither are found in GnRH neurons (67, 94, 186, 196, 218).…”
Section: Control Of Estrogen Positive Feedbackmentioning
confidence: 99%
“…The nature of progesterone signaling in Kiss1 neurons remains to be elucidated. In addition to classical nuclear PR, there are intriguing suggestions that Kiss1 neurons may have membrane progesterone receptors, especially mPRβ (136, 219). The mPRs are 7-transmembrane domain proteins that belong to the progestin and adipoQ receptor (PAQR) family, not the classic G protein-coupled receptor (GPCR) family (138,201,203).…”
Section: Control Of Estrogen Positive Feedbackmentioning
confidence: 99%